Web-Based Information System for Borrowing Practical Laboratory Equipment for The Faculty of Public Health - Ashar, Suthan Farras; Iqbal, Farhan (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
Adequate lecture facilities and infrastructure are important factors in supporting the teaching and learning process, especially at the Faculty of Public Health Sciences, State Islamic University of North Sumatra, where there is a Health Laboratory Unit with the availability of tools to support practicum activities. Lecture facilities such as practical tools and measuring instruments have a great risk of damage and loss, so a good tool loan transaction recording system is needed so that borrower data and the existence of tools can be known. With the condition of students who increase every year, the application of the manual system is no longer efficient and effective to apply. Therefore, this study focuses on the development of a web-based information system to support the laboratory equipment lending process at the Faculty of Public Health. The main results show that this system can help improve the efficiency of the equipment lending and returning process by reducing administrative barriers and providing transparency on laboratory equipment inventory data. The research process involves problem identification, system development, testing, evaluation and revision. The main problems found at the research location were such as the equipment lending process which was previously done manually, causing recording errors and data loss and lack of transparency in equipment availability so that there were often schedule conflicts or user ignorance about the status of the equipment. The system developed aims to overcome the problems that exist in the laboratory by presenting a more practical and integrated information technology-based solution.